2016
DOI: 10.1016/j.atmosenv.2016.08.050
|View full text |Cite
|
Sign up to set email alerts
|

Influence of synoptic and local atmospheric patterns on PM10 air pollution levels: a model application to Naples (Italy)

Abstract: We investigate the relationship between synoptic/local meteorological patterns and PM10 air pollution\ud levels in the metropolitan area of Naples, Italy. We found that severe air pollution crises occurred when\ud the 850 and 500 hpa geopotential heights and their relative temperatures present maximum values\ud above the city. The most relevant synoptic parameter was the 850 hPa geopotential height, which is\ud located about 1500 m of altitude. We compared local meteorological conditions (specifically wind stre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Globally, annual firework and bonfire displays during festival celebrations have been shown to generate large smoke plumes which result in a sharp increase in local PM10 levels. In Naples (Italy), for instance, high PM10 concentration events are often observed on the 1 st of January and the 17-18 th of the same month (Fortelli et al, 2016). The former is due to PM10 emissions from fireworks for New Year's celebrations, while the latter results from bonfires generated during the Saint Antony Abbot festival (Fortelli et al, 2016).…”
Section: Local Pollution Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, annual firework and bonfire displays during festival celebrations have been shown to generate large smoke plumes which result in a sharp increase in local PM10 levels. In Naples (Italy), for instance, high PM10 concentration events are often observed on the 1 st of January and the 17-18 th of the same month (Fortelli et al, 2016). The former is due to PM10 emissions from fireworks for New Year's celebrations, while the latter results from bonfires generated during the Saint Antony Abbot festival (Fortelli et al, 2016).…”
Section: Local Pollution Emissionsmentioning
confidence: 99%
“…In Naples (Italy), for instance, high PM10 concentration events are often observed on the 1 st of January and the 17-18 th of the same month (Fortelli et al, 2016). The former is due to PM10 emissions from fireworks for New Year's celebrations, while the latter results from bonfires generated during the Saint Antony Abbot festival (Fortelli et al, 2016). In India, peak PM10 concentrations are often observed during the annual Diwali celebrations in October/November.…”
Section: Local Pollution Emissionsmentioning
confidence: 99%
“…Furthermore, the results indicated that the proposed model is efficient to be applied in different countries. Fortelli et al, (2016) investigated the relationship between local metrological variables and PM10 in Naple, IItaly. Afterward, metrological variables are used to forecast PM10 for couple of days.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many studies reported increased hospital admittance for respiratory and cardiovascular diseases owing to exposure to dust storms [3,4] . In addition to the public health effects, the agriculture, air traffic, and tourism are also affected [5][6][7] . Dust storms have great environmental effects, including reduction of visibility, soil erosion, ground water salinization, and climatic change.…”
Section: Introductionmentioning
confidence: 99%